Morphometric Study of Dorsalis Pedis Artery and Variation in its Branching Pattern: A Cadaveric Study - Gupta, Chandni; Kumar, Rakesh; Palimar, Vikram; Kalthur, Sneha Guruprasad (IIUM Medical Journal Malaysia, 2018)
Introduction: Dorsalis pedis artery (DPA) is the chief artery that supplies the dorsum of the foot. Palpation of DPA at the dorsum of the foot is important in case of atherosclerotic disease. A sound knowledge of DPA like its branching pattern is essential for the ankle surgeries as well as its presence or absence in case of peripheral vascular disease. Material and methods: 30 Lower limbs of unknown age and sex were dissected in the department of Anatomy, Kasturba Medical College, Manipal. The skin and fascia were removed.The measurement of Dorsalis pedis artery till its termination, Length from medial malleolus, Length from lateral malleolus and branching pattern of Dorsalis pedis artery was studied. Results: In this study, the average length of dorsalis pedis artery was found 7.8cm, average length from medial malleolus was 3.9cm and average length from lateral malleolus was 4.5cm.The normal branching pattern of medial tarsal artery was noticed in 53% and lateral tarsal artery in 63% cases. The arcuate artery was absent in 3% of cases. Conclusion: The knowledge of the variation of DPA is helpful during various foot surgeries. Knowledge of the variation will be useful in deciding whether the absence of the pulse in DPA is due to thrombosis of the vessel or its abnormal course or absence. DPA does not always lie at mid -malleolar point.